FROM THE PERPECTIVE OF CAMGIRÇI KHAN HISTORICAL PERSONAS IN THE KIRGHIZ EPICS - Şakire BALIKÇI (Fırat University, 2019)
This work refers to the place of Camgırçı Khan in the history of the Turkish world and to the reflactions of this historical character in the Turkish epics. Meanwhile, by exemplifying other historical characters in the Turkish epics, the strong relation between literary works like epics and history is emphasized. Next, the historical role of Camgırçı Khan as the sovereign of the Astırahan is dwelled on. In the last part, based on the views of some of the researchers and historical resources it is defended that Camgırçı Khan is also a historcial character, the connection between the period of the epic and history is emphasized, and the geography where Camgırçı Khan appears in the epics is introduced.